Toward becoming a “math-person”: Relationship between achievement emotions, personal beliefs, and mathematics identity - Blažanin Barbara; Radišić Jelena; Krstić Ksenija (Psihologija)
The current study explored the relationship between mathematics beliefs (MB) (perceived competence, intrinsic value, extrinsic value and cost), academic emotions (AE) (anxiety, boredom and enjoyment), mathematics identity (MI) and mathematics achievement (MA) among eight-, nine– and ten-year-old students. The model specified in path analysis proposed that MI is associated with MB and AE. Furthermore, according to this model, MI is associated with MA and perceived competence. Results show that the model fits the data, supporting the assumed relationship between the variables and thus possibly confirming MI has a strong influence on MB. However, the relationship between MB and AE was more ambiguous. Enjoyment was the only emotion linked to mathematics identity. Finally, MA was affected by perceived competence but not by mathematics identity. The findings confirm a robust circuit of associations between intrinsic value, enjoyment and MI, signalling the importance of tracking the development of student’s interest and MI. The lack of association between MI and MA, points to the need for an educational system that prioritises mastery-oriented goals instead of achievement-oriented ones.